2022
DOI: 10.3899/jrheum.210708
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Literacy and Numeracy With Lupus Knowledge and the Creation of the Lupus Knowledge Assessment Test

Abstract: Objective Limited health literacy and numeracy are associated with worse patient-reported outcomes and higher disease activity in systemic lupus erythematosus (SLE), but which factors may mediate this association is unknown. We sought to determine the association of health literacy and numeracy with lupus knowledge. Methods Patients with SLE were recruited from an academic center clinic. Participants completed validated assessments of health literacy (Newest Vital Sign, NVS) and numeracy (Numeracy Understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several surveys investigating disease awareness among SLE patients indicate insufficient knowledge, limited access to disease-related information, and a notable lack of awareness regarding treatment medications. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several surveys investigating disease awareness among SLE patients indicate insufficient knowledge, limited access to disease-related information, and a notable lack of awareness regarding treatment medications. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Several surveys investigating disease awareness among SLE patients indicate insufficient knowledge, limited access to disease-related information, and a notable lack of awareness regarding treatment medications. 5,6 Both the economic burden faced by SLE patients and their limited understanding of disease management have a substantial impact on their attitudes, practices, and willingness to opt for biologic therapy as a treatment, as well as their active involvement in disease management, consequently impacting the prognosis of SLE patients.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Limited research in cSLE demonstrates a high prevalence of inadequate health literacy 12 while studies in adult-onset lupus show that patients with low health literacy have poor lupus-specific knowledge, and higher health literacy has been shown to influence successful transition to adult care among patients with cSLE. 13 , 14 However, health literacy in youth with cSLE and its relation to medication adherence and quality of life is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Lower health literacy was associated with worse patient-reported outcomes and higher disease activity in patients with SLE, especially in women. [9] Even after adjusting for disease activity and damage, Katz et al have reported that patients with lower health literacy had significantly poor patient-reported outcomes. [10] Knowledge and health literacy enable patients to monitor their symptoms and the disease impact.…”
Section: Introductionmentioning
confidence: 99%